Environmentally favorable Synthesis and Characterization of series of 2-hydrazinyl-3- substituted [1,8] naphthyridines (Journal of Pharmaceutical Negative Results, 2023)
A mixture of 2-aminonicotinaldehyde 1 (0.01 mol), various acetonitrile 2a-f and in the presence of KOH with MW irradiation at 200 W intermittently at 30 sec for 2.0 min to furnish 3a-f and cooled further more mixture of HCl and were added NaNO2 solution were added and stirred at RT for 5 min to afford 4a-f.this is mixed with POCl3 was exposed to MW irradiation at 200 W intermittently at 30 sec intervals for 5 min. The reaction mixture was cooled and poured onto a mixture of crushed ice and NaHCO3. The solid thus obtained was filtered, washed with water and purified by recrystallization from ethanol to give 5a-f. To this hydrazine hydrate in ethanol was refluxed on a water bath for 0.5 hr. resulting solid product was filtered, washed with water and purified by recrystallization from ethanol to afford 6a-f shown in Scheme-I. The products were further confirmed by spectral analysis.